Efek Andrographolide Oral Terhadap Biomarker Jantung pada Tikus yang Diinduksi Doxorubicin - Silmi Hanifah; Wawaimuli Arozal; Vetnizah Juniantito (Journal of Medicine and Health, 2023)
Doxorubicin remains the most prescribed anticancer agent despite its unintended side effects on non-target organs. A limiting-dose strategy is used to lower incidence of cardiotoxicity. Andrographolide has therapeutic effects including antioxidant and anti-inflammatory. This study aimed to assess cardioprotective effects of andrographolide oral on lactate dehydrogenase (LDH), creatine kinase-myocardial band (CK-MB), and relative cardiac weight in doxorubicin-induced rats. Sixteen male rats Sprague Dawley randomized into four groups: receives saline i.p and vehicle orally (Normal), doxorubicin 16 mg/kgBW i.p and vehicle orally (Dox), doxorubicin 16 mg/kgBW i.p+andrographolide 30 mg/kgBW orally (Dox+And30), doxorubicin 16 mg/kgBW i.p+andrographolide 60 mg/kgBW orally (Dox+And60). Blood was collected via cardiac puncture and cardiac organs were weighed after four-weeks administration. Total LDH and CK-MB measured spectrophotometrically. LDH and CK-MB levels significantly elevated, and signs of acute toxicity in Dox group compared with Normal group. Co-treatment with andrographolide at 30 mg/kgBW and 60 mg/kgBW reduced signs of toxicity and significantly attenuated LDH and CK-MB levels compared with Dox group (P<0.05 and P<0.01). However, body weight and relative cardiac weight were not significantly different in all groups after co-treatment with andrographolide. In conclusion, andrographolide lowered LDH and CK-MB levels, therefore has a protective potency in alleviating toxic effects of doxorubicin.